The influence of cyberloafing on library and information studies students at the University of Ibadan, Nigeria (2018)
The internet plays a vital role in the teaching and learning processes. However, the uncontrolled excessive use of these technologies by students results to several problems such as cyber loafing. This work examines the influence of cyber loafing on teaching and learning processes of students of Library and Information Studies (LIS) at the University of Ibadan (UI), Nigeria. The study adopted the descriptive survey research as the method. The questionnaire instrument was used for data collection. 100 copies of questionnaire were distributed to the librarians in training at the Department of Library, Archival and Information Studies, University of Ibadan. 99 copies were filled and returned, given a response rate of 99%. Data generated were analyzed using descriptive statistics. The findings revealed that majority of the students engage in cyberloafing and they spend an average of 5½ hours each day in cyberloafing. Whatsapp and Facebook were the major platforms that the students use to engage in cyberloafing. The students were not satisfied with their academic performance, due to the fact that cyberloafing makes them to procrastinate in their studies.